(untitled) (Research, Society and Development, 2021)
Purpose: to investigate the effects of a story-reading-aloud program on some expressiveness features in kindergarten teachers. Methods: Three preschool teachers were engaged in a simulated story-reading-aloud task and produced narrations as they normally do with their students. The narrations were audio-recorded using a Marantz professional tape recorder and an AKG microphone. Each narration was digitized individually using Praat. The effects of the programs were assessed doing the same recording procedures after the intervention. Thirty five kindergarten experienced teachers listened to the speech samples from the different moments (before and after intervention) and made comparative judgments regarding pauses, clarity, interesting, motivation and melody. Results: Results revealed that the teachers modified their speech at multiple levels. As a group, the participants demonstrated increased enunciation duration. The majority of the judges noticed statistically significant differences between the reading samples in all participants, considering the moment after intervention from the teachers as more: interesting, motivational, paused and melodic. The teachers referred positive effects from the intervention, referred in every aspect of oral expressiveness practiced. The participants reveled obtaining new vocal expressiveness knowledge after intervention and put this is use during in their work activities. Conclusion: Enunciation duration significantly increased when reading the stories aloud after intervention. The kindergarten experienced teachers, who listened the samples, noticed statistically significant differences between the reading samples and judged the moment after intervention as the best, mainly as being more paused, melodic, interesting, and motivating for children. The intervention program had a positive effect among the participants.